A search for rare B → Dμ+μ− decays - Aaij, Roel; Bachmann, Sebastian; Berninghoff, Daniel; Borsato, Martino; Caspary, Rowina; Frau, Giulia; Gerick, David; Günther, Paul André; Han, Xiaoxue; Hansmann-Menzemer, Stephanie; Hu, Jiangqiao; Kopecná, Renata; et al. (Journal of high energy physics, 2024)
A search for rare B → Dμ+μ− decays is performed using proton-proton collision data collected by the LHCb experiment, corresponding to an integrated luminosity of 9 fb−1. No significant signals are observed in the non-resonant μ+μ− modes, and upper limits of $$ \mathcal{B}\left({B}^0\to {\overline{D}}^0{\mu}^{+}{\mu}^{-}\right)<5.1\times {10}^{-8} $$, $$ \mathcal{B}\left({B}^{+}\to {D}_s^{+}{\mu}^{+}{\mu}^{-}\right)<3.2\times {10}^{-8} $$, $$ \mathcal{B}\left({B}_s^0\to {\overline{D}}^0{\mu}^{+}{\mu}^{-}\right)<1.6\times {10}^{-7} $$and $$ {f}_c/{f}_u\cdotp \mathcal{B}\left({B}_c^{+}\to {D}_s^{+}{\mu}^{+}{\mu}^{-}\right)<9.6\times {10}^{-8} $$are set at the 95 % confidence level, where fc and fu are the fragmentation fractions of a B meson with a c and u quark respectively in proton-proton collisions. Each result is either the first such measurement or an improvement by three orders of magnitude on an existing limit. Separate upper limits are calculated when the muon pair originates from a J/ψ → μ+μ− decay. The branching fraction of $$ {B}_c^{+}\to {D}_s^{+}J/\psi $$multiplied by the fragmentation-fraction ratio is measured to befcfu·BBc+→Ds+J/ψ=1.63±0.15±0.13×10−5,$$ \frac{f_c}{f_u}\cdotp \mathcal{B}\left({B}_c^{+}\to {D}_s^{+}J/\psi \right)=\left(1.63\pm 0.15\pm 0.13\right)\times {10}^{-5}, $$
The LHCb collaboration: R. Aaij, S. Bachmann, D. Berninghoff, M. Borsato, R. Caspary, G. Frau, D. Gerick, P.A. Günther, X. Han, S. Hansmann-Menzemer, J. Hu, R. Kopecna, J. Kubat, B. Leverington, J. Marks, M.P. Morgenthaler, L. Promberger, M. Schmelling, R. Skuza, D.J. Unverzagt, U. Uwer, C. Wang, L. Witola, M. Zavertyaev, Y. Zhao, A. Zhelezov [und 1036 weitere]
Die Zeichen "+" und "-" im Titel sind hochgestellt
Gesehen am 15.10.2024